Resíduos descartados como rejeitos por cooperativa de catadores: composição e análise da perda de receita - Homse, Rafael Arrobas Martins (2017)
Following the promulgation of the National Policy on Solid Waste (Law No. 12,305 / 2010), selective collection has assumed greater importance for the sustainable development of cities, since it is an activity that contributes to human and environmental health and represents the source of income Of many workers. In Londrina, the program of Selective Collection of solid waste was implemented in 1996. This program was seen as a model, recommended for implantation in other cities of the country. However, despite being a reference, many tailings still reach the system, which makes it difficult and difficult for the collectors to triage. In this way, the objective of this study was to quantify the mass of the wastes along the material collected by Cooper Region, the first cooperative of waste pickers in Londrina, in order to estimate the monthly production and to determine its gravimetric composition during 17 days of monitoring. In addition, the loss of revenue due to the failure to properly segregate the waste at source and the costs that these waste entail for the system was calculated. Finally, the economic viability of the cooperative's selective collection project was verified. It was observed that about 13% of the material that is commercialized by the cooperative is considered waste, and of this amount, materials that are recyclable but not commercially available are found, such as plastics (28%), laminate and plastic P1; Materials that are actually tailings, such as textiles (32%), diapers (1%), personal use paper (2%); And recyclable materials that in the treadmill sorting process are not picked up by the collectors and, therefore, were discarded as tailings (21%). This reject presented a loss of expressive revenue to the cooperative, a value that could be used to improve the process as a whole and would also result in a salary increase of 1,115% for the cooperative. It was observed that this project is feasible economically, but it obtained a long payback (16 years and 6 months). If the volume of tailings was zero, the return time would be approximately one year.